TRADISI ISRA’ MI’RAJ SEBAGAI UPAYA PEMBENTUKAN KARAKTER GENERASI MILLENIAL - Rifqi Muntaqo; Alfin Musfiah (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
The thesis discuss about the value of Isra' Mi'raj in the formation of character for learnerscontained in QS Al-Isra verse 1. The study motivated by how important the values of theformation character for learners contained in the event of Isra' Mi'raj Prophet MuhammadSAW The purpose of this research is: to know the values of Isra 'Mi'raj deeply in theformation of student’s character, and they can implement in their daily life. The method ofthe reserach uses the type of qualitative research in the form of library research (Libraryresearch) by taking the values of the objects Isra Mi'raj in the formation characterfor learners. The sources of data are used general and special reference sources, datacollection techniques is done by using the Library research, the technique of collectingdata by collecting data and reviewing the literature books that contain theories. Thedata analysis techniques is using content analysis techniques, namely the step in takingconclusions as an answer from the formulation of existing problems, and tahlili method isa method of interpretation that the mufasir explain the content of verses of the Qur'an invarious aspects. The results obtained from this study includes: (1) How Isra 'Mi'raj in theQur'an? Isra 'Mi'raj must be with body and soul, not dream and not imagination. ProphetMuhammad did Isra 'with the spirit and service in the conscious state. (2) What kind ofthe character values that contained in QS Al-Isra verse 1? Such as: honest, fair, patientand istiqomah. (3) How are the implications of the character values Isra 'Mi'raj in QS Al-Isra' verse 1? Praying, human is required to perform prayers, because people who alwaysperform their physical and spiritual prayers will be better, healthier, fresher than peoplewho do not perform prayers. Devoted to parents, it turns out that devote to the parents isvery influential / strategy for the formation of character the leraners. Through effectivecommunication in formulating the policy of character formation for learners and conductjoint supervision on the behavior of the learners at school and in the home environment.